Analisis Strategi Kepemimpinan Kepala Sekolah dalam Meningkatkan Kualitas Pendidikan di SMP Miftahul Huda Dzun Nurain Planggaran Timur Banyuates - Soetomo, Risqi Hartiasih; Wahidah, Wahidah; Maryanto, Maryanto (EDUPEDIA Publisher, 2025)
The quality of education in Indonesia remains a strategic issue that requires serious government attention due to its direct impact on the competitiveness of human resources in the global era. The active role of the Ministry of Education and Culture in formulating and implementing strategic policies reflects the government's commitment to addressing the complexity of national education challenges. This study aims to analyze the leadership strategies of the school principal in improving the quality of education at SMP Miftahul Huda Dzun Nurain Planggaran Timur Banyuates. The research focuses on: (1) the form of the principal’s leadership in enhancing education quality, (2) the obstacles encountered in the process, and (3) the strategic efforts undertaken to overcome them. A qualitative method with a descriptive approach was employed, using observation, in-depth interviews, and documentation as data collection techniques. The research subjects consisted of the school principal and teachers. Data analysis was conducted through data reduction, data display, and conclusion drawing. Data validity was ensured through credibility, transferability, dependability, and confirmability criteria. The findings indicate that the principal applied a democratic leadership style, provided effective supervision, and showed concern for teachers. The main challenge faced was the lack of adequate facilities and infrastructure. Improvement efforts included teacher competency development, meeting stakeholder needs, and fostering collaborative problem-solving.